Inductorless Broadband Transimpedance Amplifier for 25-Gb/s NRZ and 50-Gb/s PAM-4 Operations in a 90-nm CMOS Technology - Jou, Jau-Ji; Shih, Tien-Tsorng; Peng, Chih-Chen; Hsu, Hao-Wen; Ye, Xuan-Yi (Journal of semiconductor technology and science, 2021)
In this study, an inductorless broadband transimpedance amplifier (TIA) is implemented using TSMC 90-nm complementary metal-oxide-semiconductor (CMOS) technology. A regulated cascode circuit with low input impedance is used as the input stage of the TIA. The core amplifier is a fully differential amplifier with active feedback. The output stage of the TIA is an equalizer based on a differential amplifier with a source degenerated resistor and capacitor. The TIA has a bandwidth of 24.8 GHz and good linearity. In the TIA chip testing, clear 25-Gb/s nonreturn to zero and 50-Gb/s four-level pulse amplitude modulation eye diagrams can be observed. KCI Citation Count: 0